Building public value in hybrid e-government services: lessons from Indonesian passport service delivery - Rasona Sunara Akbar; Triyuni Soemartono; Pandji Sukmana; T. Herry Rachmatsyah (CV. Literasi Indonesia, 2026)
The digitalization of travel documents through the M-Paspor application has transformed Indonesian immigration administration. However, the hybrid nature of passport services, which combines digital registration with face-to-face verification, requires an evaluation that goes beyond technical performance toward substantive public value creation. This descriptive-exploratory qualitative study analyzes how information quality, system quality, and face-to-face service quality interact with user satisfaction to shape public value in travel document services across five Immigration Offices in Jakarta. Informants were selected purposively and consisted of 20 participants, including immigration policymakers, frontline officers, and citizen users. Data were collected through in-depth interviews, structured observations, and document review, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that accurate information and reliable systems provide administrative certainty, but public value is weakened when upload instructions, quota information, and server performance are inconsistent. In hybrid service delivery, responsive and empathetic frontline officers function as a corrective layer that converts technical convenience into satisfaction, trust, compliance legitimacy, and operational capacity. The study concludes that public value in digital immigration services is produced through the integration of reliable digital infrastructure and human-centered service quality.